Burkina Faso : Economic Development Documents. (IMF Staff Country Reports; Country Report ;, 2018)
This paper discusses various economic development documents of Burkina Faso. Economic Development Documents are prepared by member countries in broad consultation with stakeholders and development partners. They describe countries' macroeconomic, structural, and social policies in support of growth and poverty reduction, as well as associated external financing needs and major sources of financing. The aim of the 2016-2020 National Plan for Economic and Social Development (PNDES) is to structurally transform the Burkinabe economy to generate strong, sustainable, resilient, and inclusive growth in order to create decent jobs for all and improve social well-being. As a national benchmark, the plan aims to achieve cumulative growth of per capita income to reduce poverty and meet the population's basic needs within a fair and sustainable social framework. During the entire PNDES implementation phase, measures will be taken to improve the quality of institutions and strengthen the governance and the availability of qualified human resources to meet the economy's structural transformation needs.